Between the Atacama and the Sahara, between the Andes and the Atlas, a common hexagon - Montenegro Vargas, Luis Antonio (2015)
In southern Peru, specifically in the city of Tacna, one of the most representative architectural elements is called Mojinete. It can be defined as an independent construction of sober character and hexagonal; conceived under a bioclimatic conscience and handcrafted. Although it is quite widespread in the region, its origin is a mystery until today and has received little attention among researchers. The author, during a trip to the city of Marrakech, Morocco in the center of his extensive Medina, met, with a great surprise, an architectural analogy, which could be controversial and make the Mojinete an element very undervalued and would result in an example of adopting a universal architecture without major modification.